Pengaruh Dana Pihak ketiga, Non Performing Loan, Capital Adequacy Ratio, Tingkat Suku Bunga dan Arus Kas Terhadap Penyaluran Kredit Perbankan - Igarni Wau (Owner : Riset dan Jurnal Akuntansi, 2019)
The research aims to examine the effect of Third Party Funds, Non Performing Loans, Capital Adequacy Ratio, Interest Rate, and Cash Flow on Credit Distribution to Banking Companies listed on the Indonesia Stock Exchange for the period 2013-2016. Using the quantitative approach method with this type of research is descriptive quantitative. The research population and sample are 4 years or 48 months (data) Third Party Fund reports, Non-performing Loans, Capital Adequacy Ratio, Interest Rate and Cash Flow, ie from 2013-2016, with saturated sample technique sampling techniques, the analytical method used in this study is a multiple linear regression method which is done using SPSS. The results of this study show simultaneously, Third Party Funds, Non Performing Loans have a significant effect on Credit Distribution in Banking Companies on the IDX for the period 2013-2016. Partially the variables of Third Party Funds, Non Performing Loans have a significant negative effect on Credit Distribution in Banking Companies on the IDX for the period 2013-2016. Partially the variable Capital Adequacy Ratio, Interest Rate, has no significant effect on the Credit Distribution of Banking Companies on the IDX for the period 2013-2016. But the Cash Flow variable has a significant effect on Credit Distribution in Banking Companies on the IDX for the period 2013-2016. The results of the coefficient of determination analysis obtained from the R2 value of 13.8%, meaning that variations in company value can be explained from the variable Third Party Funds, Non-performing Loans, Capital Adequacy Ratio, Interest Rate, and Cash Flow of 13.8%, while the rest explained by other independent variables.